2020
DOI: 10.1155/2020/7236214
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Socioeconomic Factors and Visual Function among Patients with Age-Related Cataracts

Abstract: Background. With the development of the economy, socioeconomic factors, such as inequalities in the status of regional economies and the subsequent effects on health systems, have influenced the status of health. We explored the association between age-related cataracts and socioeconomic indicators, including the regional economy, health systems, and energy industries. Methods. This was a prospective, multicenter, Chinese population-based, cross-sectional study. A total of 830 participants from seven centers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…which could result in an underrepresentation of the glaucoma or cataract burden among the oldest age group. Additional factors such as differences in genetic predisposition across different cohorts 44 , socioeconomic status 45 , and access to healthcare services 46 may also influence the prevalence of glaucoma among individuals aged over 80 years in India. Previous studies show that diabetes is associated with different eye diseases like, retinopathy, cataract and glaucoma primarily; whereby, persons with type-1 diabetes demonstrate higher chances of retinal complications than those with type-2 diabetes 4 , 32 , 47 49 .…”
Section: Discussionmentioning
confidence: 99%
“…which could result in an underrepresentation of the glaucoma or cataract burden among the oldest age group. Additional factors such as differences in genetic predisposition across different cohorts 44 , socioeconomic status 45 , and access to healthcare services 46 may also influence the prevalence of glaucoma among individuals aged over 80 years in India. Previous studies show that diabetes is associated with different eye diseases like, retinopathy, cataract and glaucoma primarily; whereby, persons with type-1 diabetes demonstrate higher chances of retinal complications than those with type-2 diabetes 4 , 32 , 47 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Lens opacity is the main cause of cataract, and surgical treatment is the main way to fight against cataract. 10 However, the main cause of the recurrence of cataract is the surgical treatment. For cataract, targeted therapy has the potential advantages of less side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that rates of blindness are higher in rural areas with low economic growth and high levels of poverty. In comparison to their urban counterparts, there are more visually impaired women in rural areas (Dandona et al, 2001; Finger et al, 2012; Wan et al, 2020). For instance, research in rural India revealed that women, poor, rural residents and patients aged 70 or older who underwent cataract surgery had less than ideal visual outcomes (Fant, 2017).…”
Section: Introductionmentioning
confidence: 99%